Evaluation of CA125 in relation to pain symptoms among adolescents and young adult women with and without surgically-confirmed endometriosis. - Naoko Sasamoto; Mary DePari; Allison F Vitonis; Marc R Laufer; Stacey A Missmer; Amy L Shafrir; Kathryn L Terry (PLoS ONE, 2020)
Endometriosis is a painful gynecologic disease affecting one in ten reproductive aged women worldwide. Few studies have correlated this symptomatology with biomarker levels among women with and without endometriosis, and no studies correlating pain with biomarker levels have been performed in young patient populations. The purpose of this study was to examine whether CA125 correlates with different types and severity of pain among adolescents and young women with and without endometriosis and assess its performance as an endometriosis biomarker among those presenting with dysmenorrhea in this young population. Reproductive-aged women with laparoscopically-confirmed endometriosis (n = 282) and controls (n = 293) who participated in The Women's Health Study: From Adolescence to Adulthood (A2A), a cohort of adolescents and young women enrolled from 2012-2018, were included in this cross-sectional analysis. Plasma CA125 values were measured using WERF EPHect compliant blood samples collected at enrollment. Average CA125 were calculated by self-reported pain type (i.e. dysmenorrhea, non-cyclic/general pelvic pain, dyspareunia), severity, and frequency in endometriosis cases and controls. Median age at blood draw was 24 years in controls and 17 years in cases, with 68% and 89% non-Hispanic white, respectively. Most endometriosis cases (95%) were rASRM stage I/II. Average CA125 values were 12.5 U/mL in controls and 12.1 U/mL in cases adjusted for age. CA125 did not differ by pain type, its severity, or frequency in endometriosis cases or controls. Among participants who reported dysmenorrhea, CA125 did not discriminate endometriosis cases from controls using cutoff of 35 U/mL (AUC = 0.51, 95%CI = 0.50-0.53). Among adolescents and young adult women, CA125 did not correlate with pain type. CA125 did not efficiently discriminate endometriosis cases from controls even when accounting for pain symptomatology. Average CA125 values were low in adolescents and young women in both endometriosis cases and controls, suggesting cautious interpretation may be needed when measuring CA125 in this population.